Chloroplast Genome Evolution of Hamamelidaceae at Subfamily Level - Yanlei Liu; Kangjia Liu; Wenpan Dong; Shunping Dong; Yiheng Wang; Chao Xu; Enze Li; Jiahui Sun (Ecology and Evolution, 2025)
ABSTRACT The Hamamelidaceae is significant for its contributions to construction, furniture making, and ornamental use, including 26 genera and 119 species. However, complete chloroplast genome sequences of Hamamelidaceae species have been reported less frequently. In this study, five species were newly sequenced, and seven others available complete chloroplast genomes were added to compare the chloroplast genome evolution in Hamamelidaceae at the subfamily level. The results indicated that the chloroplast genome size ranged from 158,116 to 159,941 bp, encoding 79 to 81 protein‐coding genes, four ribosomal RNA genes, and 30 to 31 transfer RNA genes. A robust phylogenetic tree of Hamamelidaceae was obtained using complete chloroplast genomes, supporting that all Hamamelidaceae species formed a monophyletic group and divided into four subfamilies. Exbucklandioideae was the first diverged group within Hamamelidaceae, followed by Mytilarioideae, Disanthoideae, and Hamamelidoideae, which formed a clade. Furthermore, three new potential DNA barcodes were provided: trnH‐psbA, psbJ‐petA, and ycf1. This study confirms that the complete chloroplast genome data provide a more accurate and confident resolution of the phylogenetic relationships within the Hamamelidaceae. These new genomic data not only enhance the understanding of genome evolution but also provide a better understanding of the phylogenetic relationships of Hamamelidaceae.